Price and Marketing Information in Chili Farmers Communications Network in Indonesia - Gandasari, Dyah; Musyadar, Achmad (International Journal of Engineering and Technology, 2018)
Fluctuations in price and the nature of chilli that can easily damaged lead to chili farmers need accurate and reliable information to improve its marketing. It is interesting to study the communication network of chili farmers in the process of collecting information on the price and marketing. The purpose of this research is to analyze the communication network of price and marketing information of the chilli farmers in Pacet District of Cianjur Regency, West Java Indonesia. The communication network is analyzed using UCINET 6 analysis tools and individual analysis unit. The results of the study shows that: 1) the communication network structure is centralized or interlock personal network, 2) the source of information (star) is the chairman of the farmers group or farmers group association who works as a trader, 3) the average values of out-degree and in-degree is about 1.276 and 1.394.Â Â Â